2008
DOI: 10.1063/1.3037227
|View full text |Cite
|
Sign up to set email alerts
|

Modeling bulk and surface Pt using the “Gaussian and plane wave” density functional theory formalism: Validation and comparison to k-point plane wave calculations

Abstract: We present a study on structural and electronic properties of bulk platinum and the two surfaces (111) and (100) comparing the Gaussian and plane wave method to standard plane wave schemes, normally employed for density functional theory calculations on metallic systems. The aim of this investigation is the assessment of methods based on the expansion of the Kohn-Sham orbitals into localized basis sets and on the supercell approach, in the description of the metallicity of Pt. Electronic structure calculations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 92 publications
3
22
0
Order By: Relevance
“…The validity of the CP2K package as accurate G-point only approach has been validated through a systematic supercell approach for the calculation of transition metal surface properties. 27,28 Three different unit cells comprising 36, 56 and 90 gold atoms have been built and employed throughout the study. The unit cells were shaped to obtain in all cases three layers of Au(111) surface when the period boundary conditions are imposed over an orthorhombic simulation cell.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The validity of the CP2K package as accurate G-point only approach has been validated through a systematic supercell approach for the calculation of transition metal surface properties. 27,28 Three different unit cells comprising 36, 56 and 90 gold atoms have been built and employed throughout the study. The unit cells were shaped to obtain in all cases three layers of Au(111) surface when the period boundary conditions are imposed over an orthorhombic simulation cell.…”
Section: Computational Detailsmentioning
confidence: 99%
“…They found that the phase diagram was qualitatively similar to the 3D system. Santra et al [23] in 2008 studied the nucleation rate of a liquid phase. They used the LJ model and Monte Carlo simulations to validate the predictions of the classical nucleation theory.…”
Section: Introductionmentioning
confidence: 99%
“…However, we have verified with a number of tests that the variation in binding energy of a probe adsorbate (H atom) is <0.02 eV after dipole correction or with the use of a seven‐layer non‐stoichiometric slab model. The computed work function for the (0 0 0 1) and (1 0 true1 0) α‐WC surfaces is 5.1 and 4.9 eV, respectively, which can be compared with that of the Pt(1 1 1) surface of 5.7–5.8 eV …”
Section: Resultsmentioning
confidence: 98%